Weeds as alternative useful medicinal source: Mimosa pudica Linn. on diabetes mellitus and its complications - Tunna, Tasnuva Sarwar; Ahmed, Qamar Uddin; Helal Uddin, A.B.M.; Sarker, Md. Zaidul Islam (Trans Tech Publications, Switzerland, 2014)
Diabetes mellitus is one of the major reasons for mortality worldwide and numerous scientific studies are going on to find plausible solutions to overcome and manage diabetes and its related infirmities. Traditional medicines use medicinal plants as anti-diabetic agents and despite being a disturbing weed to farming land Mimosa pudica Linn. has a high traditional usage for various purposes including anti-diabetic complications. The objective of this article is to accumulate and organise literatures based on traditional claims and correlate those with current findings on the use of M. pudica in the management of diabetes mellitus. M. pudica is a creeping perennial shrub which is a common weed widely distributed in Southeast Asia specially in India, Bangladesh, Malaysia, China, Philippine etc. This plant has various species of which M. pudica is a well recognised plant of medicinal origin which has been traditionally used as folk medicine in India, Bangladesh and Philippine, Chinese, herbal and siddha medicines. It has wound healing, antidiabetic, anti-diarrhoeal, antimicrobial, anti-cancer, anti-infections, anti-worm, anti-proliferative, anti-snake venom, anti-depressant and anxiolytic etc. activities. The objective of this article is to provide up-to-date information on the traditional and scientific studies based on this plant on the frontier of diabetes mellitus. The methodology followed was to methodically collect, organise and chart the recent advances in the use of M. pudica in diabetes and its related complications like vascular complications, diabetic wound, hyperlipidemia etc. Various scientific studies and traditional literatures clearly support the use of M. pudica as an anti-diabetic agent among other uses. So far, the anti-diabetic compounds have not been isolated from this plant and this can be a good scientific study for the future anti-diabetic implications.